2019
DOI: 10.1155/2019/7315714
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Effectiveness of High-Intensity Interval Training in Hypoxia and Normoxia in Healthy Male Volunteers: A Pilot Study

Abstract: Aims. The study investigated the effect of high-intensity interval training in hypoxia and normoxia on serum concentrations of proangiogenic factors, nitric oxide, and inflammatory responses in healthy male volunteers. Methods. Twelve physically active male subjects completed a high-intensity interval training (HIIT) in normoxia (NorTr) and in normobaric hypoxia (HypTr) (FiO2 = 15.2%). The effects of HIIT in hypoxia and normoxia on maximal oxygen uptake, hypoxia-inducible factor-1-alpha, vascular endothelial g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 63 publications
1
23
0
1
Order By: Relevance
“…The organism's desire to adapt to high-altitude effort could be particularly evident in the behavior of TRP fluorescence at an altitude of 5000 m when the value of its emission after 24 hours has approached the value before the effort in normoxia. Recently, beneficent adaptation to exercise by high-intensity interval training in hypoxia because of a significant increase concentration of HIF-1 α and NO levels in the serum using biochemical methods was reported [47].…”
Section: Discussionmentioning
confidence: 99%
“…The organism's desire to adapt to high-altitude effort could be particularly evident in the behavior of TRP fluorescence at an altitude of 5000 m when the value of its emission after 24 hours has approached the value before the effort in normoxia. Recently, beneficent adaptation to exercise by high-intensity interval training in hypoxia because of a significant increase concentration of HIF-1 α and NO levels in the serum using biochemical methods was reported [47].…”
Section: Discussionmentioning
confidence: 99%
“…In a human study, eight weeks of resistance training (twice per week, five sets of 10 repetitions at 70% of pretraining one-repetition maximum, separated by 90 s of rest between sets) was performed in normoxic and hypoxic conditions (F i O 2 of 14.4%, equivalent to 3000 m) [ 105 ], the plasma VEGF protein and capillary-to-fibre-ratio increased only after hypoxic resistance training [ 105 ]. A recent study investigated the effect of HIIT on the serum concentrations of pro-angiogenic factors in hypoxia, and found that HIIT alone resulted in a significant increase in exercise-induced elevations in serum VEGF, but exercise in hypoxia did not further influence the VEGF levels [ 106 ].…”
Section: Skeletal Muscle Molecular Response To Hypoxiamentioning
confidence: 99%
“…Exercise, particularly at higher intensities, is also known to promote angiogenesis and vasodilation, partly to regulate temperature. 96 Therefore, caution with exercise prescription is required to mitigate the increased risk of bleeding while using anticoagulation agents in patients with enhanced bleeding risk and to prevent injury and further complications. Antiviral agents previously used to treat influenza have been reported to be effective for treating COVID-19.…”
Section: Covid-19 Pharmaceutical Agents and Exercisementioning
confidence: 99%